IDENTIFIKASI PRAKTIK PENGELOLAAN LAHAN AGROFORESTRI KELOMPOK TANI HUTAN KEMASYARAKATAN DI KECAMATAN TONGAUNA UTARA KABUPATEN KONAWE: Identification of Agroforestry Land Management Practices by Community Forest Farmers' Groups In North Tongauna District, Konawe Regency - Agus setiawan; Arniawati; Muhammad Saleh Qadri; Ridwan Adi Surya; Sahindomi Bana; Davik; Zulkarnain; Alamsyah Flamin; La Ode Muhammad Erif; Mariana Zainun (Jurusan Kehutanan -FHIL-UHO, 2025)
Abstract: Agroforestry is a strategy in community forest management that plays an important role in land conservation and food provision. The purpose of this study was to determine the characteristics of farmers, the classification of agroforestry systems, the application of agroforestry patterns, and the types of plants that make up the agroforestry land of farmer groups in Andalambe Village, North Tongauna District, Konawe Regency. This study used a descriptive qualitative and quantitative approach, interviews, and field observations. The descriptive method was used to describe the classification of agroforestry system implementation, agroforestry patterns, and types of plants in the study location. The results showed that the agroforestry classification applied by farmers was the agrisilviculture system, with 27% of farmers applying the alternate rows agroforestry pattern and 73% applying the random mixture agroforestry pattern. The types of plants used in agroforestry included forestry plants, plantation plants, and agricultural plants, with a total of fourteen types of plants recorded. The types of plants used were dominated by those for forest and land conservation (23%) and for sustainable local food supply (20%). This study is expected to contribute to the development of a community-based agroforestry forest management model to support forest and land conservation and sustainable food supply.